Negative Density-dependent Dispersal in Tsetse Flies: A Risk for Control Campaigns?. Issue 8 (August 2019) - De Meeûs, Thierry; Ravel, Sophie; Solano, Philippe; Bouyer, Jérémy
Abstract : Tsetse flies are vectors of parasites that cause diseases responsible for significant economic losses and health issues in sub-Saharan Africa, including sleeping sickness in humans and nagana in domestic animals. Efficient vector-control campaigns require good knowledge of the demographic parameters of the targeted populations. In the last decade, population genetics emerged as a convenient way to measure population densities and dispersal in tsetse flies. Here, by revealing a strong negative density-dependent dispersal in two dimensions, we suggest that control campaigns might unleash dispersal from untreated areas. If confirmed by direct measurement of dispersal before and after control campaigns, area-wide and/or sequential treatments of neighboring sites will be necessary to prevent this issue. Highlights: A strongly negative density-dependent dispersal was found in tsetse fly populations. Reducing tsetse fly densities may unleash dispersal and recolonization from neighboring sites. The long-term benefits of control campaigns may be jeopardized as a result.